DETERMINANTS RELATED TO LUNG TUBERCULOSIS IN THE WAY OFPUBLIC HOSPITAL ANUTAPURA - Erfan AR. Lainjong (LPPM Universitas Bina Mandiri Gorontalo, 2022)
Pulmonary Tuberculosis (pulmonary TB) is an infectious airborne disease caused by the bacterium Mycobacterium tuberculosis, which affect the lower respiratory tract. Education level, smoking, income, and family history were known as risk factors for pulmonary TB. The purpose of this study was to determine the determinants associated with pulmonary TB in the outpatient department of Anutapura General Hospital, Palu. This research was an analytical study with a cross-sectional design. The independent variables in this study were the level of education, smoking status, income, and family contact history, while the dependent variable was pulmonary TB. We enrolled 43 respondents with accidental sampling method. Data analysis using univariate and bivariate analysis. The results showed that there was a relationship between education level and pulmonary TB (p = 0.024), smoking status and pulmonary TB (p = 0.004), income and pulmonary TB (p = 0.001), and family contact history with pulmonary TB (p = 0.001).There is a relationship between education level, smoking status, income, and family contact history with pulmonary TB. It is suggested to the health workers of RSU Anutapura Palu to increase understanding and knowledge of patients regarding the prevention and transmission of pulmonary TB disease.